Language-Based Strategies that Support Person-Centered Communication in Formal Home Care Interactions with Persons Living with Dementia. (April 2023) - Mundadan, Reanne G.; Savundranayagam, Marie Y.; Orange, J. B.; Murray, Laura
Language-based strategies are recommended to improve coherence, clarity, reciprocity, and continuity of interactions with persons living with dementia. Person-centered care is the gold standard for caring for persons with dementia. Person-centered communication (PCC) strategies include facilitation, recognition, validation, and negotiation. Little is known about which language-based strategies support PCC in home care. Accordingly, this study investigated the overlap between language-based strategies and PCC in home care interactions. Analysis of conversation of 30 audio-recorded interactions between personal support workers (PSWs) and persons living with dementia was conducted. The overlap between PCC and language-based strategies was analyzed. Of 11, 347 communication units, 2578 overlapped with PCC. For facilitation, 21% were yes/no questions. For recognition, 25% were yes/no questions and 22% were affirmations. For validation, 81% were affirmations and positive feedback. Finally, 60% were yes/no questions for negotiation. The findings highlight the person-centeredness of language-based strategies. PSWs should use diverse language-based strategies that are person-centered.